PENGARUH PEMBELAJARAN DAN KAPABILITAS TEKNOLOGI INFORMASI TERHADAP KINERJA BISNIS (Studi pada Industri Besar-Menengah di Semarang) (Jurnal Dinamika Informatika, 2010)
PENGARUH PEMBELAJARAN DAN KAPABILITAS TEKNOLOGI INFORMASI TERHADAP KINERJA BISNIS (Studi pada Industri Besar-Menengah di Semarang) Purwatiningtyas Fakultas Teknologi Informasi Universitas Stikubank Semarang Email : diba_ian@yahoo.com Abstrak: The concept of organization learning has recenty enjoyed a renaissance among both academics and practitioners seeking to Improve organizations. Althogh a large body a research theoretically assets a positive relationship between organizational learning and information technology and strong relationship between information technology and business performance, the seemingly  relationship between organizational learning and business performance has yet not been fully expored. This paper examincs the mediating role of information technology capability (IT capability) in the relationship between organization learning and business performance. The basic resrcarch question is how does organization learning increase business performance via IT capability.   Kata kunci :